Al-Ruwda Al-Kadhimiya And its Endowments between 1921-1958 - Zuwayed, Shorouq Abdul-Sadah; Al-Mousawi, Raja Zamil Kazem (Al-Adab Journal, 2021)
The holy Kadhimiya Alrowad is one of the most important places in the city of Baghdad, and it is one of the centers that carried the banner of defense and jihad against the British occupation, and forms the nucleus that the souls of Muslims from most cities and Islamic countries as well as researchers, has been surrounded by interest from successive governments as well as from lovers and those who have Her dignities, so the Holy Alrowad took a rectangular shape that includes a number of the facility and included the remains of the companions, which included caring for the Holy Alrowad and its associated buildings with continuous restoration, maintenance, and decking until it reached splendor and creativity that takes its visitors to calmness of soul and transmits reassurance in them.